2009
DOI: 10.1089/cap.2008.0143
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Response in Depressed Adolescents With and Without Co-Morbid Attention-Deficit/Hyperactivity Disorder in the Treatment for Adolescents with Depression Study

Abstract: Objective: In the Treatment for Adolescents with Depression Study (TADS), fluoxetine (FLX) and the combination of fluoxetine with cognitive-behavioral therapy (COMB) had superior improvement trajectories compared to pill placebo (PBO), whereas cognitive-behavioral therapy (CBT) was not significantly different from PBO. Because attention-deficit= hyperactivity disorder (ADHD) and major depressive disorder (MDD) frequently co-exist, we examined whether ADHD moderated these outcomes in TADS. Method: A total of 43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 31 publications
(17 reference statements)
1
17
1
Order By: Relevance
“…Consistent with other large recent CBT trials, all youth were required to meet Diagnostic and Statistical Manual of Mental Disorders criteria for major depression at baseline. However, depression severity was somewhat lower in this sample (baseline CDRS-R mean = 53.2, SD 9.3) than in other trials such as TADS (mean = 60.0, SD 10.4) 54 or TORDIA (mean = 59.0, SD 10.0). 55 That our sample was slightly less depressed is not surprising, given that these youth were initially identified as depressed in primary care.…”
Section: Discussioncontrasting
confidence: 66%
“…Consistent with other large recent CBT trials, all youth were required to meet Diagnostic and Statistical Manual of Mental Disorders criteria for major depression at baseline. However, depression severity was somewhat lower in this sample (baseline CDRS-R mean = 53.2, SD 9.3) than in other trials such as TADS (mean = 60.0, SD 10.4) 54 or TORDIA (mean = 59.0, SD 10.0). 55 That our sample was slightly less depressed is not surprising, given that these youth were initially identified as depressed in primary care.…”
Section: Discussioncontrasting
confidence: 66%
“…reported contradictory findings about the effect of comorbid ADHD on depressive response, with two studies reporting an adverse effect Rohde et al 2001) and two others not reporting on it (Herman et al 2007;Kratochvil et al 2009). As recently reviewed, observational studies have provided more consistent evidence that comorbid ADHD worsens the long-term course of depression (Daviss 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Interviewers went through extensive training to validly administer the K-SADS-PL, including reviewing and re-rating at least three other trained interviewers' taped or live interviews, then having other trained interviewers review and re-rate their taped or live interviews. Using all available information, primary interviewers made a best estimate of adolescents' current and previous diagnoses, using guidelines recommended for ADHD, depression, and other pediatric diagnoses (Leckman et al 1982). Consistent with others' recommendations, greater weight was typically given to child reports of internalizing symptoms, and to parent and teacher reports of ADHD and other externalizing symptoms (Happonen et al 2002).…”
Section: Diagnostic and Other Proceduresmentioning
confidence: 99%
“…Data from these analyses suggested that comorbid ADHD did not negatively affect CBT response in adolescents with depression. 120 Likewise, in a clinic-based study of adolescent anxiety disorders, comorbid ADHD did not affect CBT treatment outcomes. 121 Thus, there is some reason to suggest that larger clinic-based trials for CBT in adolescent ADHD may be worthy of consideration.…”
Section: Clinic-based Cognitive-behavioral Treatment For Adolescentsmentioning
confidence: 93%